Ship stability for masters and mates - Barrass, C.B (Butterworth-Heinemann, 2012)
Understanding ship stability - the ability of a ship to return to an initial state after disturbing forces and moments - is critical for all maritime students and professionals studying for a deck or engineering certificate of competency, or seeking promotion to a higher rank within marine or naval companies or institutions. The seventh edition of this classic text provides a comprehensive introduction to all aspects of ship stability and ship strength, squat, interaction and trim, materials stresses and forces, with numerous worked examples to assist masters, mates and engineering officers with qualifications and professional practice. New coverage includes content on new materials used in ship construction, developing methods of propulsion and the latest research into resistance. Ship Stability for Masters and Mates is required reading for seafarers and students alike and an important resource for naval architecture students, shipboard officers and shore-based staff, including dry-dock personnel, ship-designers, ship surveyors, port authorities, marine consultants and superintendents. Updated throughout to include new shipping industry developments and regulations, with 9 new chapters, the latest ship stability datasheets, and sample exam questionsProvides a comprehensive introduction to all aspects of ship stability and ship strength, squat, interaction and trim, materials stresses and forcesConcepts are supported with numerous worked examples, clear diagrams, graphs and equations to assist with understanding and application of this critical subject.